Gabriel de Ávila Othero, Eduardo Kenedy. Sintaxe, Sintaxes, uma introdução São Paulo: Editora Contexto. 2015, 221 p. ISBN 978-85-7244-915-1 - Brito, Ana Maria (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2020)
.